Developing educational curricula in the Sultanate Oman in light of the skills of the Fourth Industrial Revolution - Almashaikhi, Basma Nasser Mohamed; Alsaiari, Mashael Awadh (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to reveal the requirements for designing educational curricula in light of the skills of the Fourth Industrial Revolution era. It also aimed to reveal the most important challenges associated with those skills. The study ended up with a number of suggestions to align educational curricula with the skills of the Fourth Industrial Revolution. The study used the descriptive approach by reviewing the relevant literature. The results of the study showed that there are a number of requirements associated with enhancing skills, improving teaching and learning methods, and strengthening community partnership. The results also revealed some challenges related to weakness in educational policies, knowledge, and technical aspects. The study reached to a number of suggested procedures such as the development of the teachers, the students, and the classroom environments.